Turkey’s Pursuits Of Alternative Gas Suppliers: Central Gas Hub Project? - Mehmet Ferhat Fırat (European Scientific Journal, ESJ, 2016)
Energy has always been the most crucial issue on the world’s political agenda and it is likely to remain so in the future. In recent years, changing dynamics of world politics has made the ‘energy security’ the number-one topic on the international relations. At theoretical level, dependency on one country for energy supply has been regarded as a leverage of one country over another. Thus, in this scope, diversification of energy suppliers has inevitably become a topic of academic and political discussions. As a result, diversification of not only energy suppliers but also energy routes has gained significance. In this sense, the diversity of energy transition routes is the essential part of the energy security issue (The IEA defines energy security as “the uninterrupted availability of energy sources at an affordable price”). This creates an opportunity for the countries like Turkey which occupy a geostrategic position to provide a secure transportation route by means of pipeline systems. At this juncture, this paper examines Turkey’s efforts and potentials in diversifying source country and automatically energy routes for the purpose of increasing the energy security. Thus, forthcoming sections of the paper will touch firstly upon why Turkey has still potential to be central gas hub because of geostrategic position. Then, alternatives source countries will be analyzed.